Effect of 20% ethanol extract of Subang pineapple gel on oral mucosa incisional wound length - Indah Puti Rahmayani Sabirin; Amanda Debora Polii; Rahmadaniah Khaerunnisa; Euis Reni Yuslianti; Ris Kristiana (Padjadjaran Journal of Dentistry, 2022)
ABSTRACT